El sistema geográfico de información y las concentraciones de plomo en sangre en una población infantil venezolana Usefulness of the Geographic Information System (GIS) in the identification of contributing factors to lead blood concentrations in a population of Venezuelan children - Carlos Espinosa; Maritza Rojas; David Seijas (Instituto Nacional de Salud Pública, 2006)
OBJETIVO: Identificar los factores ambientales que contribuyen a la concentración de plomo en sangre (Pb-S) en niños de Valencia, Venezuela, con la utilización del Sistema Geográfico de Información (SGI). MATERIAL Y MÉTODOS: Estudio analítico ecológico. Población: 60 niños. Información obtenida: demografía, fuentes de emisión de plomo ambiental, niveles de Pb-S. Relación entre variables ambientales y Pb-S mediante análisis de buffer. RESULTADOS: Diferencia significativa entre el Pb-S en varones (11.1±3.1 µg/dl) en comparación con las mujeres (9.5±2.7 µg/dl). La media de la Pb-S de los niños residentes en buffer (10.7±3.2 µg/dl) fue superior a la media de los restantes (9.9±2.5 µg/dl). Los niños con valores superiores al límite permisible de Pb-S que viven en la zona sur tuvieron una media de Pb-S significativamente superior respecto de los demás. El SGI permitió identificar en el taller de herrería/soldadura la fuente de exposición más cercana a las residencias de los varones. CONCLUSIONES: El SGI hizo posible reconocer fuentes de exposición al plomo y su vínculo con niveles de Pb-S de los niños que viven cerca de dichas fuentes. Se sugiere evaluar con posterioridad los factores adicionales que favorecen el riesgo de exposición. OBJECTIVE: To identify environmental factors that contribute to blood lead levels (BPb) in children living in an urban area in Valencia, Venezuela, using a Geographical Information System (GIS) as an association tool. MATERIAL AND METHODS: An analytical-ecological study was carried out. Population: 60 children. Data collected: Demography, potential sources of environmental lead and BPb concentrations. An association was made between environmental variables and BPb, using a buffer analysis. RESULTS: There was a statistically significant difference between BPb in males (11.1±3.1 µg/dl) compared to females (9.5±2.7 µg/dl). Average BPb of children living within the buffer areas (10.7±3.2 µg/dl) was higher than that of the rest of the children (9.9±2.5 µg/dl). Children with BPb levels higher than the permissible limit who live in the southern region of the area studied had an average BPb significantly higher than the rest. The GIS enabled the identification of a soldering/welding shop as the nearest source of exposure to the male children´s homes. CONCLUSIONS: GIS made it possible to recognize sources of lead exposure in the area and its association with the BPb levels of children that live near such sources. It is suggested to further evaluate additional factors that could influence the risk of lead exposure.